On (n,m)-Groups for n>2m - Galić, Radoslav (Sarajevo Journal of Mathematics, 2024)
In this article a theorem about a (2m,m)-group of Čupona-Dimovski is generalized. 2000 Mathematics Subject Classification. Primary: 20N15.